Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1177/000313481408001117
|View full text |Cite
|
Sign up to set email alerts
|

Liver Abscess Secondary to Acute Appendicitis: How a Chicken Bone Started it All

Abstract: Brief Reports should be submitted online to www.editorialmanager.com/ amsurg. (See details online under ''Instructions for Authors''.) They should be no more than 4 double-spaced pages with no Abstract or sub-headings, with a maximum of four (4) references. If figures are included, they should be limited to two (2). The cost of printing color figures is the responsibility of the author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…[ 1 ] The sequence of PLA secondary to rupture of acute appendicitis has been reported. [ 3 ] Occasionally, PLA occurred from surgical or penetrating wounds. Recently, a study demonstrated the significant change in etiology of PLA, which is predominantly caused by Klebsiella pneumoniae and occurred in patients with underlying hepatobiliary disease that spread directly from biliary infection.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] The sequence of PLA secondary to rupture of acute appendicitis has been reported. [ 3 ] Occasionally, PLA occurred from surgical or penetrating wounds. Recently, a study demonstrated the significant change in etiology of PLA, which is predominantly caused by Klebsiella pneumoniae and occurred in patients with underlying hepatobiliary disease that spread directly from biliary infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although acute appendicitis is a common emergency disease (7%) [8] , appendicitis with pyogenic liver abscess is rare, with an estimated incidence of less than 0.03% [1] . In most cases, liver abscess metachronously occurs after the start of treatment for a perforated, gangrenous, or phlegmonous appendicitis [2] , [9] , [10] . In a previous report, liver abscess was caused by organisms via the following three major routes: the biliary tract (60%), portal vein (6%), and hepatic artery (10%) [11] .…”
Section: Discussionmentioning
confidence: 99%